To Implant or not to Implant?: The Role of Imaging - M, Shruthi; R, Sangeetha; Singh, Ashish Kumar; Kini, Raghavendra; Naik, Vathsala (Journal of Orofacial Research, 2013)
Missing teeth are best replaced by implants, provided the implant is placed in a way that it fulfills esthetic, functional and biomechanical requirements. The assessment of the proposed implant site requires a very specific and accurate data. This could be accomplished by various imaging modalities starting from two-dimensional traditional radiographs to three-dimensional computed tomography and cone beam computed tomography. The purpose of this article is to provide an overview of different imaging modalities, the type of imaging best suited at different time frames of implant placement and effective radiation dose to the patient in these imaging modalities.